IMAGINING NATIONALISM ACROSS BORDERS: The Malay Identity of Border Communities in the Batam Archipelago - Fauzi, Fauzi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study examines the construction of nationalist identity among border communities in the Batam Archipelago, Indonesia, focusing on the role of transnational Malay identity in shaping national allegiance. Drawing on Benedict Anderson’s theory of imagined communities, transnationalism, and cultural identity theory, this research investigates how border residents navigate their dual affiliations to the Indonesian state and the wider Malay world. Employing a qualitative-interpretive methodology, data were collected through in-depth interviews, participant observation, and secondary sources. The findings reveal an ambivalent form of nationalism in which Indonesian identity is co-constructed alongside a broader Malay consciousness. Cultural continuity, kinship networks, and economic interdependence with Malaysia and Singapore reinforce a transnational sense of belonging that transcends formal state borders. While the Indonesian state maintains symbolic and administrative authority in the region, everyday practices reflect a fluid, negotiated nationalism shaped by regional proximity and historical ties. This study contributes to the literature on border studies and nationalism by highlighting the complexities of identity formation in Southeast Asian maritime frontiers.